I. BERGERA (ed.) - Lucien Hervé, España blanca y España negra / White Spain and Black Spain - Marina Barba, Jesús; Morón Serna, Elena (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2020)
Iñaki Bergera (ed.) Lucien Hervé, España blanca y España negra / White Spain and Black Spain Madrid: Turner, coeditado con el Ministerio de Fomento, Arte y Foto Series, 2019. 244 pages. Softcover with flaps, two volumes. Language: Spanish and English. 24 €. ISBN-13: 978-8417866013